1993
DOI: 10.1128/aem.59.8.2364-2368.1993
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of Escherichia coli O157:H7 in ground, roasted beef as affected by pH, acidulants, and temperature

Abstract: A study was undertaken to determine the fate of Escherichia coli 0157:H7 in ground, roasted beef as influenced by the combined effects of pH, acidulants, temperature, and time. There was essentially no change in the viable population of E. coli 0157:H7 when beef salads (pH 5.40 to 6.07) containing up to 40%o mayonnaise were incubated at 5°C for up to 72 h. At 21 and 30°C, significant (P 5 0.05) increases in populations of the organism occurred in salads containing 16 to 32% mayonnaise (pH 5.94 to 5.55) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(60 citation statements)
references
References 34 publications
5
55
0
Order By: Relevance
“…Buchanan and Klawitter (1991) demonstrated that at 12°C, E. coli O157 : H7 grew in Brain Heart Infusion broth adjusted to pH 5·5 with HCl. The resistance of E. coli O157 : H7 to acid is unexceptional for a Gram-negative organism, and has also been demonstrated by others (Brackett et al 1994 ;Podolak et al 1996) during storage after acid decontamination, in fermented meat at pH 4·5 (Glass et al 1992) and in lactic acid-acidified (pH 5·4-6·1) beef salads (Abdul-Raouf et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Buchanan and Klawitter (1991) demonstrated that at 12°C, E. coli O157 : H7 grew in Brain Heart Infusion broth adjusted to pH 5·5 with HCl. The resistance of E. coli O157 : H7 to acid is unexceptional for a Gram-negative organism, and has also been demonstrated by others (Brackett et al 1994 ;Podolak et al 1996) during storage after acid decontamination, in fermented meat at pH 4·5 (Glass et al 1992) and in lactic acid-acidified (pH 5·4-6·1) beef salads (Abdul-Raouf et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Foodborne pathogens such as Escherichia coli O157:H7 and Salmonella typhimurium are important micro-organisms (Andrew and Ray 1989;Karmal 1989;Dickson and Anderson 1991;Abdul-Raouf et al 1993;Dickson and Siragusa 1994;Clavero and Beuchat 1995;McCleer and Rowe 1995;Rochelle et al 1996). To control those foodborne pathogens, several interventions or chemicals have been used and applied (Abdul-Raouf et al 1993;Davey and Smith 1989;Dickson and Anderson 1991;Barkate et al 1993;Zhao et al 1993;Dickson and Siragusa 1994;Dorsa et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne pathogens such as Escherichia coli O157:H7 and Salmonella typhimurium are important micro-organisms (Andrew and Ray 1989;Karmal 1989;Dickson and Anderson 1991;Abdul-Raouf et al 1993;Dickson and Siragusa 1994;Clavero and Beuchat 1995;McCleer and Rowe 1995;Rochelle et al 1996). To control those foodborne pathogens, several interventions or chemicals have been used and applied (Abdul-Raouf et al 1993;Davey and Smith 1989;Dickson and Anderson 1991;Barkate et al 1993;Zhao et al 1993;Dickson and Siragusa 1994;Dorsa et al 1996). These interventions include organic acid sprays (generally lactic or acetic acids), hot water/steam treatments and antimicrobial chemical applications such as chlorine, chlorine dioxide, and trisodium phosphate (Abdul-Raouf et al 1993;Davey and Smith 1989;Dickson and Anderson 1991;Barkate et al 1993;Zhao et al 1993;Dickson and Siragusa 1994;Siragusa 1995;Dorsa et al 1996;Rochelle et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1986;March and Ratnam 1986). However, this medium has been shown to perform poorly when heat-stressed, acidstressed (Abdul-Raouf et al 1993) or freeze-stressed (Conner and Hall 1994) cells of E. coli 0157: H7 are present. It is important that any detection method used for this organism takes account of injured cells not only because E. coli 0157 : H7 has a very low infective dose (Lior 1994) but also because injured cells, in general, retain their pathogenic traits and a proportion of the population in food is liable to be in the injured state as a result of processing operations or subsequent storage.…”
Section: Introductionmentioning
confidence: 99%